Development Of Bimetallic Catalyst Ni-Co/MgO-ZrO2 For Reforming Of Methane Using Carbon Dioxide - Fan , Mun Sing (2010)

(untitled)
Carbon dioxide reforming of methane (CDRM) is a potential method to utilize the greenhouse gases (CO2 and CH4) to produce syngas as the feedstock for the production of liquid fuel through Fischer-Tropsch process. Nickel (6 wt% Ni), cobalt (6 wt% Co) and Ni-Co (3 wt% Ni and 3 wt% Co) supported over mesoporous MgO-ZrO2 as catalysts were prepared using a surfactant assisted-impregnation method. CDRM process using these catalysts were studied in a quartz tube microreactor at 750 °C, 1 atm with gas hourly space velocity of 125,000 mL/g/h. Based on reactant’s conversion and syngas yield in the product stream, bimetallic catalyst Ni-Co/MgO-ZrO2 (NCMZ) was a suitable catalyst for carbon dioxide reforming. The bimetallic catalyst exhibited high and stable activity during 40 h reaction time with methane and carbon dioxide conversions of 80 % and 84 %, respectively. The syngas ratio was close to unity, without significant deactivation as compared to the respective monometallic catalysts. The bimetallic catalyst also exhibited excellent regenerability by restoring its initial catalytic activity through 1 h of regeneration treatment in air. The high performance of the catalyst was due to better metal dispersion, small metal particle size and synergetic effect between Ni and Co particles.